The Relationship between Stress – Coping – Resilience in Children with Diabetes - Cucui, Corina (Didactica Danubiensis, 2023)
The article underlines the close connection between the stress associated with the chronic disease, the cognitive or behavioral strategies used to reduce the unpleasant emotions generated by the disease and resilience as an attitude and ability to overcome the disabling chronic disease condition in children with type I diabetes, considering the fact that the aim is to determine the child's well-being and normalcy without majorly affecting his functioning. Resilience involves the association of experiences, thoughts with the difficult situation and involves the action of all internal resources to restore balance and the state of adaptation in a positive way, so that the child with diabetes can face strong emotions, but also have a normal development. The environment with which they interact is particularly important for the child as it favors a series of adequate or inadequate coping strategies. As children grow, their cognitive strategies for emotional regulation improve and help determine their coping style in stressful situations. In order to be able to observe the effects of stress in children with diabetes, we must analyze their own way of adapting to the disease from the perspective of their psychosocial functioning. Diabetes and stress seem to be interconnected, so that stress can be both the cause and the direct consequence of diabetes-related problems. Emotional stress can affect hormone levels, disrupting insulin physiology. Thus, the triad of perceived stress - coping - resilience leads us to a state of well-being and to an increase in the quality of life.